Sintesis Analog Kurkumin (2E,6E)-2-(4-Hidroksi-3-Metoksi-5-((Pirolidin)metil)benziliden) -6-(4-Metoksibenziliden)Sikloheksan-1-on - Rahmawati, Nur; Fitriana, Adita Silvia; Sholikha, Munawarohthus (Sainstech Farma: Jurnal Ilmu Kefarmasian, 2023)
Curcumin is a potential compound to be developed. However, the clinical use of these compounds is limited due to their low stability and bioavailability. Therefore, to increase the pharmacological activity of curcumin, it is necessary to modify the chemical structure of curcumin. Curcumin analog compound (2E,6E)-2-(4-hydroxy-3-methoxy-5-((pyrrolidine)methyl)benzylidene)-6-(4-methoxybenzyliden)cyclohexane-1-on can be synthesized in 3 steps. Phase I, the reaction between p-methoxybenzaldehyde and cyclohexanone took place aldol condensation reaction with NaOH catalyst. Phase II, the Clasein-Schmidt reaction between compound 1 (the result of the synthesis of stage I) and vanillin involved dilute HCl as the catalyst. Phase III, reacting the results of the synthesis of phase II with Mannich pyrrolidine base by adapting the method used by Geschickter and Maeadow. Compound 3 as a result of purification was observed using Thin Layer Chromatography using Ethyl Acetate:Methanol (1:1) as an eluent to obtain Rf 0.46 and a melting range of 130-131 oC. The yield obtained was 51.52% with the characteristics of a reddish brown powder. This compound needs further identification using the Mass Spectrum and NMR.